A quantum-chemical study of oxygen-vacancy defects in PbTiO3 crystals - Stashans, A. (2006)
Investigation of an oxygen vacancy and F center in the cubic and tetragonal lattices of PbTiO3 crystals is done by means of quantum-chemical simulations. Displacements of defect-surrounding atoms, electronic and optical properties, lattice relaxation energies and some new effects due to the defects presence are reported and analyzed. A comparison with similar studies is made and conclusions are drawn on the basis of the obtained results. © 2006 Elsevier B.V. All rights reserved.